Arabic Mufradat Learning Throught Anagram Media - Siregar, Sri Dewi Priwarti; Asep Sopian; Nunung Nursyamsiyah (Shaut al Arabiyyah, 2024)
Abstract: This study explores the problems that are still difficult for students in learning Arabic, namely the motivation to memorize and master mufradat. Most students are initially excited to learn, but then become bored and lazy. The research method used in this study is a literature study with a qualitative approach. By using this method, the researcher uses a discussion about anagram games in the form of journals and papers to add data in the form of previous research on vocabulary learning. through observation with Arabic teachers, anagram media is suitable to be applied in learning Arabic, anagrams can increase students’ interest in language and indirectly increase CBSA levels in the teaching and learning process. This is because the activities carried out by students in this language game are not only physical activities but also mental activities. Anagrams are puns, phrases, or sentences that create new meaning when words, phrases, or sentences are rearranged. In general, words that can be anagrammed should be at least 4 letters long because they are easy to confuse with new words, but there are many words with less than 4 letters.